Depression in the Chinese aging population: leveraging cultural humility to improve the quality of care of a vulnerable population. (December 2011) - Dong, XinQi; Chang, E-Shien; Simon, Melissa
Depression is a global public health problem, with broad social, economic and personal consequences. However, there exists incomplete understanding of the psychological distress of Chinese older adults, which is often exacerbated by the cultural and linguistic barriers at the individual, family and community levels. This paper reviews the epidemiology of depression among Chinese older adults and also explores the barriers to treatment. Since depression in the Chinese aging population is a multifaceted issue, a culturally appropriate and interdisciplinary approach to improve the quality of life and quality of care for the Chinese older adults is critical. We propose that leveraging cultural humility models in conjunction with existing cultural competency training could be a novel strategy to enhance training of healthcare professionals dealing with depression in Chinese aging populations. Future research is needed to explore the causal mechanism and consequences associated with depression in representative Chinese aging populations.